Gestión empresarial para confecciones maná sports - Espinoza Shigui, Maryuri Margoth (2016)
The present research project was developed with the objective of implementing a business management model that allows improving the organizational and productive development of “Confecciones Maná Sports”, a microenterprise dedicated to the manufacture of sportswear, which brings on serious problems due to the lack of business management that directs appropriately its organizational structure, strategic planning and operational processes. The investigative methods used for the development of the project were the inductive, analytical and synthetic, which allowed identifying the weaknesses of an administrative process. In addition, questionnaires were used as tools to carry out the interview to the owner manager, customers’ survey and also an observation sheet for collection of essential information for research. The results gotten when applying these tools and investigative techniques are reflected in the determination of the micro-business situation; where the opportunities, weaknesses and threats were detected that directly affect the management. The production and service processes of the enterprise was designed through flow charts, it was proposed a business management design to follow through the EFQM model which is focused.